Synthesis and electroactivity of pyrrole end-functionalized poly(2-methyl-2-oxazoline) - Cirpan, A.; Alkan, S.; Toppare, L.; David, G.; Yagci, Y. (Elsevier BV, 2001)
Poly(2-methyl-2-oxazoline) (PMeOZO) with pyrrole end groups was synthesized by cationic ring polymerization of 2-methyl-2-oxazoline initiated by benzyl bromide and subsequent modification of the halide end group. The structure and electroactivity of the macromonomer thus obtained were confirmed by spectral analysis and cyclic voltametry, respectively. The posssibility of chemical and electrochemical graft copolymerization of PMeOZO with pyrrole was also studied.